The road not taken : a documented biography of Randall Thompson - Schmidt, Carl B.; Schmidt, Elizabeth K. (Hillsdale, NY : Pendragon Press, 2018)
Thompson's works, presented chronologically and given RT numbers, are described based on information gleaned from correspondence, diaries, personal interviews with his family, friend, and colleagues, newspaper reviews, the composer's own program notes, recordings, and assorted other sources. Extensive performance histories on the more important works are provided, and every known performance which Thompson himself conducted or attended is cited. In addition, conductors who particularly championed Thompson's works are given emphasis in the commentary and lists of performances--Back cover.
Cover has this book being number 5 in the series. The publisher's website has conflicting information, but title page has No. 6.
Includes bibliographical references and index.
Keywords: Thompson, Randall, -- 1899-1984.; 1900-luku; Composers -- United States -- Biography; säveltäjät; taidemusiikki; kuoromusiikki; uskonnollinen musiikki; henkilöhistoria; Yhdysvallat; elämäkerrat